KONDISI KEHIDUPAN DAN ANALISIS LAPORAN UNRWA DI GAZA DALAM PERSPEKTIF KONVENSI GENOSIDA 1948 - Maulana Zikri; Yenni Rosana (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
This study analyzes living conditions as an indicator of genocide risk in Gaza from the perspective of Human Security and examines its relevance to the elements outlined in the 1948 Genocide Convention. The research employs a qualitative approach using a case study method through document analysis of reports from the United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA) from 2015 to 2017. The findings indicate that the humanitarian situation in Gaza is characterized by restrictions on humanitarian aid, destruction of civilian infrastructure, and increasing physical and psychological suffering among civilians. These conditions create multidimensional vulnerabilities affecting personal, economic, food, health, and community security. From the perspective of the Genocide Convention, such conditions may correspond to indicators described in Article II (b) and (c), particularly actions causing serious bodily or mental harm and the creation of living conditions that could lead to the destruction of a group. However, this study does not assess the presence of genocidal intent (dolus specialis), which remains a key legal element distinguishing genocide from other international crimes. The study also shows that these humanitarian vulnerabilities had emerged during the 2015–2017 period and remain relevant in understanding the continuing humanitarian crisis in Gaza today.